Switching Chemoselectivity: Using Mechanochemistry to Alter Reaction Kinetics. (8th November 2018) - Howard, Joseph L.; Brand, Michael C.; Browne, Duncan L.
Abstract: A reaction manifold has been discovered in which the chemoselectivity can be altered by switching between neat milling and liquid assisted grinding (LAG) with polar additives. After investigation of the reaction mechanism, it has been established that this switching in reaction pathway is due to the neat mechanochemical conditions exhibiting different kinetics for a key step in the transformation. This proof of concept study demonstrates that mechanochemistry can be used to trap the kinetic product of a reaction. It is envisaged that, if this concept can be successfully applied to other transformations, novel synthetic processes could be discovered and known reaction pathways perturbed or diverted.